2018
DOI: 10.3390/ma11040491
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and Photocatalytic Properties of BiSnSbO6 under Visible Light Irradiation

Abstract: BiSnSbO6 with strong photocatalytic activity was first fabricated by a high-temperature, solid-state sintering method. The resulting BiSnSbO6 was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), UV-vis diffuse reflectance spectroscopy (DRS) and X-ray photoelectron spectroscopy (XPS). The results showed that BiSnSbO6, with a pyrochlore structure and a cubic crystal system by a space group Fd3m, was well crystallized. The lattice parameter or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 72 publications
2
5
0
Order By: Relevance
“…From Fig.9(b), (c), (d), it can be concluded that the BiSnSbO 6 -ZnO composite photocatalytic material, the forbidden band widths of BiSnSbO 6 and ZnO materials are 2.81 eV, 2.66 eV and 3.14 eV, respectively. This is similar to the data reported in the previous literature (J. F Luan et al 2018)…”
supporting
confidence: 93%
See 1 more Smart Citation
“…From Fig.9(b), (c), (d), it can be concluded that the BiSnSbO 6 -ZnO composite photocatalytic material, the forbidden band widths of BiSnSbO 6 and ZnO materials are 2.81 eV, 2.66 eV and 3.14 eV, respectively. This is similar to the data reported in the previous literature (J. F Luan et al 2018)…”
supporting
confidence: 93%
“…In the ZnO spectrum, the characteristic peaks at 2θ = 31.1°, 34.0°, 35.6°, 47.0°, 56.0°, 62.3° and 67.5°c orrespond to (100), (002), (101), (102), (110), (103) and (112) crystal planes, the same as the ZnO standard card (PDF#01-0562), are wurtzite hexagonal phases (V.Kononenko et al 2017; A. Sundararaj et al 2017). The characteristic diffraction peaks located at 2θ = 29.4°, 34.0°, 48.9°, 58.0°, 60.8° and 71.8°c orrespond to (222), (400), (440), (622), (444) and (800) of BiSnSbO 6 diffraction crystal plane, which is consistent with the literature report (J. F Luan et al 2018)…”
supporting
confidence: 92%
“…Materials containing antimony have received increasing attentions mainly due to their interesting physical properties and potential applications in nonlinear optics, electrochemistry and photocatalysis, e. g., in recent years. [1][2][3][4][5][6][7][8] In the antimony compounds, a number of irregular SbO n (n = 3, 4, 5, 6) coordination geometries can be found, such as trigonalpyramidal SbO 3 , seesaw SbO 4 , square-pyramidal SbO 5 , or distorted octahedral SbO 6 . [9][10][11][12][13] Benefiting from the diversity and flexibility of its structure, SbÀ O units can construct various novel crystal structures by selecting functional building blocks to exhibit special physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Materials containing antimony have received increasing attentions mainly due to their interesting physical properties and potential applications in nonlinear optics, electrochemistry and photocatalysis, e. g., in recent years [1–8] . In the antimony compounds, a number of irregular SbO n (n=3, 4, 5, 6) coordination geometries can be found, such as trigonal‐pyramidal SbO 3 , seesaw SbO 4 , square‐pyramidal SbO 5 , or distorted octahedral SbO 6 [9–13] .…”
Section: Introductionmentioning
confidence: 99%
“…When the R factor was less than 20%, it meant that the XRD experimental test data of the sample was in good agreement with the theoretical data. 37 In this paper, the R factor of pure GaOOH prepared by us was only 9.85%, revealing that the pure GaOOH was prepared successfully with a orthorhombic crystal system and a space group Pbnm, and the lattice parameters of pure GaOOH were a ¼ 4.509526Å, b ¼ 9.771034Å and c ¼ 2.969284Å, which was almost consistent with the reported results (orthorhombic, Pbnm, a ¼ 4.5545Å, b ¼ 9.8007Å and c ¼ 2.9738Å). 38 The rst ve peaks at 2q ¼ 21.76 , 34.00 , 35.41 , 37.46 and 54.54 were all observed clearly for pure GaOOH and Ba-doped GaOOH in Fig.…”
Section: Resultsmentioning
confidence: 99%